Correlates of high-impact physical activity measured objectively in older British adults. (11th December 2017) - Elhakeem, Ahmed; Hannam, Kimberly; Deere, Kevin C; Hartley, April; Clark, Emma M; Moss, Charlotte; Edwards, Mark H; Dennison, Elaine; Gaysin, Tim; Kuh, Diana; Wong, Andrew; Fox, Kenneth R; et al.
Abstract: Background: Exposure to higher magnitude vertical impacts is thought to benefit bone health. The correlates of this high-impact physical activity (PA) in later life are unknown. Methods: Participants were from the Cohort for Skeletal Health in Bristol and Avon, Hertfordshire Cohort Study and MRC National Survey of Health and Development. Associations of demographic, behavioural, physiological and psychological factors with vertical acceleration peaks ≥1.5 g (i.e. high-impact PA) from 7-day hip-worn accelerometer recordings were examined using linear regression. Results: A total of 1187 participants (mean age = 72.7 years, 66.6% females) were included. Age, sex, education, active transport, self-reported higher impact PA, walking speed and self-rated health were independently associated with high-impact PA whereas BMI and sleep quality showed borderline independent associations. For example, differences in log-high-impact counts were 0.50 ( P < 0.001) for men versus women and −0.56 ( P < 0.001) for worst versus best self-rated health. Our final model explained 23% of between-participant variance in high impacts. Other correlates were not associated with high-impact activity after adjustment. Conclusions: Besides age and sex, several factors were associated with higher impact PA in later life. Our findings help identify characteristics of older people that might benefit from interventions designed to promote osteogenic PA.